Khiyar in Buying and Selling Online Based on the Fiqh Perspective - Novita, Dwi; El-Falahi, Luthfi; Putra, Haris Maiza (AL-ISTINBATH : Jurnal Hukum Islam, 2022)
The problem of fiqh continues to develop toward the progress of the times, the purpose of this study is to examine the comparison of fiqh about buying and selling connected between the concept of fiqh in Islam and buying and selling online. The method in this study uses a qualitative method with literature or library research. The research materials were obtained from the books, scientific journals, and the internet related to fiqh comparisons about buying and selling. The results of the study showed that Islam clearly regulates buying and selling, related to online buying and selling in the form of e-commerce through online buying and selling applications, it is legal as long as the business does not contain prohibited elements. Online sales transactions where the goods are only based on the description provided by the seller are considered valid, but if the description of the goods does not match then the buyer has the right of khiyar which allows the buyer to continue the purchase or cancel it. The practice of khiyar in e-commerce transactions can be seen in the form of the consumer's ability to return goods, returned goods can be exchanged for similar goods or ask for a refund that has been paid.